2017
DOI: 10.1155/2017/3083745
|View full text |Cite
|
Sign up to set email alerts
|

Methods in Ranking Fuzzy Numbers: A Unified Index and Comparative Reviews

Abstract: Fuzzy set theory, extensively applied in abundant disciplines, has been recognized as a plausible tool in dealing with uncertain and vague information due to its prowess in mathematically manipulating the knowledge of imprecision. In fuzzy-data comparisons, exploring the general ranking measure that is capable of consistently differentiating the magnitude of fuzzy numbers has widely captivated academics' attention. To date, numerous indices have been established; however, counterintuition, less discrimination,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 88 publications
(145 reference statements)
5
34
0
Order By: Relevance
“…In the same scenario, the weight coefficients of the remaining assessment index were each reduced by the corresponding ratios. Changes in the ranking of the alternatives for the scenarios are shown in Tables 25-27. e results (Tables [25][26][27] show that the allocation of different weights to the assessment index through the scenarios leads to a change in the ranking of the alternatives, which confirms that the model is sensitive to changes in the weight coefficients. By comparing the alternatives which are ranked first (Alter.…”
Section: Sensitivity Analysismentioning
confidence: 62%
See 1 more Smart Citation
“…In the same scenario, the weight coefficients of the remaining assessment index were each reduced by the corresponding ratios. Changes in the ranking of the alternatives for the scenarios are shown in Tables 25-27. e results (Tables [25][26][27] show that the allocation of different weights to the assessment index through the scenarios leads to a change in the ranking of the alternatives, which confirms that the model is sensitive to changes in the weight coefficients. By comparing the alternatives which are ranked first (Alter.…”
Section: Sensitivity Analysismentioning
confidence: 62%
“…Multicriteria decision-making (MCDM) [23,24] by using the experience and wisdom of experts is a feasible method to comprehensively consider the multidimensional influencing factors and their coupling relationship that affect the green performance evaluation. In the existing similar evaluation problem and its solution, the value or importance of a factor is usually evaluated by one expert in numerical number form, which is unreasonable due to the preferences 2 Complexity of individual expert and the fuzziness of expert judgment [25,26]. Additionally, the green performance evaluation of intelligent manufacturing includes multidimensional influencing factors with complex coupling relationship, and these factors and their relationship are dynamic evolution.…”
Section: Introductionmentioning
confidence: 99%
“…It was known that FAHP with TpFN numbers was the generalization of FAHP with TFN numbers [60], also had a better rank according to the expert opinions. Also, based to the unified index for comparing fuzzy numbers TFN and TpFN [61], [60] was shown that the trapezoidal FAHP method is the most suitable one, as it provides the most accurate results when compared to other methods.…”
Section: Comparison Results For Questions Levelmentioning
confidence: 99%
“…These indices the information of climatic anomalies make more comprehensible and may be used to determine the severity, the temporal and spatial extent of drought. These three elements constitute the three dimensions of drought (Guttmann 1998;Hayes 2000;Nohegar & Heydarzadeh 2016).…”
Section: Introductionmentioning
confidence: 99%